PREVALENCE OF DISC DISPLACEMENTS WITH REDUCTION IN TEMPORO-MANDIBULAR JOINT IN YOUNG PEOPLE – A PRELIMINARY STUDY - Andreea Kui; S. Buduru; Mariana Pacurar; I. Socaciu; A. Berar; S. Balhuc; A. Ciurea; M. Negucioiu (Romanian Journal of Medical and Dental Education, 2020)
Aims. This preliminary study had as objective to assess the prevalence of Disc Displacements with Reduction (DDwR) among young patients and to determine if there is any correlation between abnormal muscular activity or occlusal modifications and the presence of DDwR. Material and Methods. 25 patients were examined, chosen based on the following inclusion criteria: age between 20 and 40 years old, good general health condition, without any other systemic pathology. Each subject underwent clinical examination associated with the completion (within the anamnesis) of a questionnaire that included inquiries regarding the presence of vicious habits (the presence of bruxism, oral breathing, and unilateral mastication). Results. In this preliminary study, the age range of the patients was between 22 and 37 years, 15 women and 10 men. Based on the clinical findings and correlated with the axiography results, 14 subjects were diagnosed with DDwR; for those subjects, clicks were the most frequent symptom. The results also showed that 43% of the subjects felt pain during the mandible movements. The endooral examination also revealed the existence of gingival retractions in 50% of the subjects. Intraoral modification and the presence of noises (clicking) were the most often signs and symptoms, even for young patients. Conclusions. The prevalence of DDwR among women is higher. One of the most common symptoms is the clicking (the noise) the patient perceives during opening and closing the mouth and muscular pain. All the DDwR patients presented occlusal premature contacts and interferences during the eccentric movements of the mandible.